A TYK2 Gene Mutation c.2395G>A Leads to TYK2 Deficiency: A Case Report and Literature Review - Wu, Peilin; Chen, Suqing; Wu, Bin; Chen, Junhong; Lv, Ge (Frontiers in Pediatrics, 2020)
Tyrosine kinase 2 (TYK2) deficiency was formerly defined in patients suffering from autosomal recessive hyperimmunoglobulin E syndrome (AR-HIES). In recent years, it was proposed that human TYK2 deficiency is probably not a common cause of the AR-HIES but a distinctive illness object. In the current work, a recessive TYK2 deficiency is reported in a patient suffering from BCG disease and recurrent respiratory infection. Whole exome sequencing of the genome implied that this patient carried novel missense homozygous mutation (c.2395G> A, p. G799R) in the TYK2. By literature review, we summarized the clinical manifestations, gene mutations and related cytokine responses of formerly reported patients possessing TYK2 deficiency. The core manifestation of these patients are infected by intracellular pathogens, such as mycobacteria and/or viruses. Therefore, the possibility of TYK2 deficiency should be considered when a patient has repeated intracellular bacteria (including tuberculosis bacillus infection), repeated viral infection or eczema.